3(2x-7+5x)=x-1

Simple and best practice solution for 3(2x-7+5x)=x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-7+5x)=x-1 equation:


Simplifying
3(2x + -7 + 5x) = x + -1

Reorder the terms:
3(-7 + 2x + 5x) = x + -1

Combine like terms: 2x + 5x = 7x
3(-7 + 7x) = x + -1
(-7 * 3 + 7x * 3) = x + -1
(-21 + 21x) = x + -1

Reorder the terms:
-21 + 21x = -1 + x

Solving
-21 + 21x = -1 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-21 + 21x + -1x = -1 + x + -1x

Combine like terms: 21x + -1x = 20x
-21 + 20x = -1 + x + -1x

Combine like terms: x + -1x = 0
-21 + 20x = -1 + 0
-21 + 20x = -1

Add '21' to each side of the equation.
-21 + 21 + 20x = -1 + 21

Combine like terms: -21 + 21 = 0
0 + 20x = -1 + 21
20x = -1 + 21

Combine like terms: -1 + 21 = 20
20x = 20

Divide each side by '20'.
x = 1

Simplifying
x = 1

See similar equations:

| F(x)=12x^2+24 | | H=-16t^2+128t+5 | | -6a-36=-4(3a+3) | | 3x+129= | | -7y=-21+28 | | 1/2(x-5)=x-2 | | 4x+3/-5x-3=-1/2 | | 6v-5+5=6v | | (2x^2+6x-7)+(4x^2+2x+17)-(6x^2-11)= | | -4(4-7b)-3(4b-6)=-30 | | 6(x-2)-2x=-40 | | -147=-7(3-3r) | | A=3X(-1) | | 1+5m+7=-7 | | t*-1.5=8 | | -4*-1.5=6 | | -8(p-5)=109.6 | | 4-3x=4(3-x)-3x | | -0.1875*8=-1.5 | | (x^2+5x+5)-(5x^2-8x+7)= | | 8*t=-1.5 | | -4.45-2=-5.5s-4.2 | | -7k-5(-7k+7)=-3+4(7-8k) | | 6*t=-9 | | 6*(-9)=t | | -(h+7)=-8 | | 12-4n=-(n+1)-5 | | (12y+14)+(-2y-3)= | | x/3+18=44 | | 10+x+5x=7x+2 | | 2x+33-5x=3-7x+2 | | (9x-1)-(4x+3)= |

Equations solver categories